First report of rust on onion caused by Puccinia allii in Korea. (13th December 2021) - Kwon, Jin-Hyeuk; Kang, Byeongsam; Moon, Jin-Seong; Choi, Okhee; Lee, Yeyeong; Kim, Jinwoo
Abstract: In August 2018, rust was observed on onions ( Allium cepa ) grown in Dalseong, South Korea. In the field where the rust occurred, the disease incidence exceeded 60%. The urediniospores produced on diseased leaves were globose to ellipsoid and 20‒30 × 20‒28 μm in size. They had a thick outer wall (1‒2 μm) and many spines were apparent on the surface under light microscopy. When the uredinium was mature, the epidermis of the onion leaf ruptured to expose many yellow to dark red urediniospores, appearing as a powder. DNA sequencing and phylogenetic analysis of the internal transcribed spacer (ITS) region confirmed that the isolate was Puccinia allii . Based collectively on the morphological characteristics and molecular identification, the causal fungus was identified as P. allii . This is the first report of rust caused by P. allii on onion in Korea, a disease that may constitute a serious threat to production of this crop in Korea.